Din ve Toplumsal Kurumlar Arası İlişkilerdeki Tamamlayıcı Niteliğin Önemi - Eyüpoğlu, Osman; Perşembe, Erkan (Journal of History Culture and Art Research, 2019)
The Relationship Between Religion and Social Institutions: A Functionalist Approach Abstract The institutions consisting a society can be classified sociologically by six basic institutions such as family, education, religion, economy, politics, and spare time. A society can only exist through complemented relations between these institutions. Each institution meets a basic need of society. When all these institutions fulfill their duties, all societal needs are met in a balanced way. For this reason, it is expected that a harmony should be between these institutions that serve to the same aim. If any society can exist as a whole, this situation shows that there is naturally a harmony between those institutions. Therefore, there should be a complemented quality between these institutions. In case of social changes, it is seen negatively that religion is generally abstracted by other social institutions. In fact, it is expected that those who perform these applications should act according to the scientific realities. Social and historical realities have indicated that the institution of religion is not an institution that contains discourses against to the society called as superstructure, but it is an institution that provides an ontological legitimacy to which all institutions need. For this reason, in case we act in accordance with these social realities in all of our social arrangements, we take advantage maximum from all of those institutions, especially in the institution of religion. Hence, there is a complemented relation between religion and society or between religion and the world or between the world and the next world. Öz Toplumu oluşturan kurumlar sosyolojik anlamda, aile, eğitim, din, ekonomi, siyaset ve boş zaman olmak üzere altı temel kurum üzerinden sınıflandırılabilir. Bu kurumlar arasındaki işlevsel tamamlayıcı ilişki sayesinde toplum var olabilmektedir. Her bir kurum toplumun temel bir ihtiyacına cevap vermektedir. Tüm kurumlar görevlerini icra ettiklerinde bütün ihtiyaçlar da dengeli bir biçimde karşılanmış olmaktadır. Bu sebeple aynı amaca hizmet eden kurumlar arasında bir uyum olması beklenir. Toplum bir bütün olarak var olabiliyorsa, bu durum onu oluşturan kurumlar arasında da bir uyumun doğal olarak var olduğunu göstermektedir. Bu nedenle toplumsal kurumlar arasındaki ilişkinin tamamlayıcı bir niteliğe sahip olması işin doğası gereğidir. Toplumsal değişme durumlarında genellikle dinin diğer toplumsal kurumlardan soyutlanması gibi olumsuz uygulamalar gözlemlenmektedir. Bu uygulamaları icra eden iradelerin bilimsel realitelere uygun hareket etmesi beklenir. Sosyolojik ve tarihsel realiteler göstermiştir ki din kurumu, toplum dediğimiz üst yapıya aykırı söylemler içeren bir sistem değil; aksine toplumsal kurumların hepsinin muhtaç olduğu ontolojik meşruiyeti onlara sağlayan bir kurum olmaktadır. Bu nedenle tüm toplumsal düzenlemelerimizde bu sosyolojik realitelere uygun olarak hareket ettiğimiz takdirde, bütün kurumlardan ve özellikle din kurumundan en azami derecede yararlanmış oluruz. Çünkü din ile toplum arasında veya din ile dünya ya da dünya ile ahiret arasındaki ilişkinin doğal niteliği birbirlerini tamamlayıcı olmalarıdır.